The personality of women in the texts of the Emirati theater (Journal of the College of Basic Education, 2023)
The character of women in the Emirati theatrical text occupied an important space of the theater text and performance, as most of the Emirati playwrights were writing their plays and they are well aware that women in their texts are a reflection and representation of the general social situation, because of their alignment with social, political and economic developments. No playwright can sculpt the image of women in their text without relying on the basic cultural references of the text through content, based on the principle of the complementarity of life, when the personality of a woman is a complementary/balancing element of the personality of a man. They, in turn, create continuity of life through a direct relationship between them. Many Emirati playwrights have been interested in establishing themes that cared about women, and the philosophy of their texts was based on them as in Tawfiq al-Hakim, Saadallah and Nous, the researcher and through the goal he envisages in his research to put Emirati women as an artistic image in the Emirati text, and through the relationship of this with society found, that there is a problem that exists ...